Broad Antibody and Cellular Immune Response From a Phase 2 Clinical Trial With a Novel Multivalent Poxvirus-Based Respiratory Syncytial Virus Vaccine. (29th July 2020) - Jordan, Elke; Lawrence, Steven J; Meyer, Thomas P H; Schmidt, Darja; Schultz, Stephanie; Mueller, Jutta; Stroukova, Daria; Koenen, Brigitte; Gruenert, Robert; Silbernagl, Guenter; Vidojkovic, Sanja; Chen, Liddy M; et al.
Abstract: Background: Respiratory syncytial virus (RSV) is a major cause of severe respiratory disease in young children and the elderly. Protective immunity is not generated after repeated infections, but vaccination may hopefully prove effective. Methods: This phase 2 clinical study investigated a multivalent RSV vaccine (MVA-BN-RSV) designed to induce broad antibody and cellular immune responses by encoding RSV surface proteins F, G (for both A and B subtypes), and internal antigens (M2, N). This study evaluated the immune response in adults aged ≥55 years to identify the optimal MVA-BN-RSV dose and vaccination schedule. Results: A single dose increased the levels of neutralizing (plaque reduction neutralization test to RSV A and B) and total (IgG and IgA ELISA) antibodies (1.6 to 3.4-fold increase from baseline) and induced a broad Th1-biased cellular immune response (interferon-γ ELISPOT) to all 5 vaccine inserts (5.4 to 9.7-fold increases). Antibody responses remained above baseline for 6 months. A 12-month booster dose elicited a booster effect in antibody and T-cell responses (up to 2.8-fold from preboost levels). No drug-related serious adverse events were reported. Conclusions: MVA-BN-RSV induces a broad immune response that persists at least 6 months and can be boosted at 12 months, without significant safety findings. Clinical Trials Registration: NCT02873286 Abstract : The novel multivalent RSV vaccine MVA-BN-RSV, based on the MVA-BN vector, induces a broad antibody and cellular immune response in older adults that persists at least 6 months and can be boosted at 12 months, without significant safety findings.